Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1966
DOI: 10.1177/000331976601701102
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Brain Damage in Dogs Due To Systemic, Induced Hypotension and Head-Up Tilt for Short Periods

Abstract: In the evaluation of various procedures designed to protect the brain against hypoxic damage, an objective and, if possible, quantitative assessment of the brain damage is necessary. Further investigations of these problems are indicated, among other reasons, because of recent developments in cardiovascular and neurologic surgery which may be complicated by temporary or permanent brain damage. Since the dog has been the principal experimental animal in these fields, this animal was chosen for the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…21 To date, many investigators have recognized systemic hypotension as one of the most important factors in hypoxic-ischemic stress which cause perinatal brain damage. 22 Animal studies using sheep, 23 monkeys, 24 piglets, 25 and dogs 26 showed a strong association of histological change in the brain following systemic hypotension. Meanwhile, there have been many stud- Figure 1 The three grades of brain damage by MAP-2 disappearance in the surface areas of the cerebral cortex, hippocampus and thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…21 To date, many investigators have recognized systemic hypotension as one of the most important factors in hypoxic-ischemic stress which cause perinatal brain damage. 22 Animal studies using sheep, 23 monkeys, 24 piglets, 25 and dogs 26 showed a strong association of histological change in the brain following systemic hypotension. Meanwhile, there have been many stud- Figure 1 The three grades of brain damage by MAP-2 disappearance in the surface areas of the cerebral cortex, hippocampus and thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…79 Most of these studies had a high mortality during the early hours following hypotension whether or not brain lesions were produced. 2 -*" 9 The present study had 3 major goals: 1) to produce focal or diffuse brain injury in monkeys exposed to hypotension in the absence of significant hypoxemia, hypercarbia, or acidosis, 2) to attain survival for intermediate or prolonged periods, and 3) to correlate various parameters of the hypotensive insult with outcome with respect to the brain and the cardiovascular system.…”
Section: Neuropathologic Findingsmentioning
confidence: 99%